Digital Storytelling as a Means of Education and Formation of Spiritual and Ethical Values in Adolescence (on the Base of Classic Literature Material) - T.A. Poskakalova (Moscow State University of Psychology and Education, 2023)
The article presents the results of the study that identifies the possibilities of applying activity technologies in education to create digital stories for the purposes of formation of spiritual and ethical values in adolescents. The study took place in March, 2023, on the basis of MBOU SOSH school No. 4 in Kashira town, 38 schoolchildren of the 7th grade aged 13-14 years old took part in it. As part of the study, during three sessions 9 cartoons were created in the stop-motion animation technique, they were based on the literary material of A.P. Chekhov. The article presents an analysis of the production process of animation products creation, it also discusses the aspects of the formation of spiritual and moral values ​​while creating cartoons. The article also focuses on the empirical data that demonstrate the peculiarities of the adolescents’ perception of joint activities when working on cartoons and according to the degree of motivation for the activity. The study proves the effectiveness of the use of practices for creating digital stories by adolescents for establishing interpersonal communication, appropriating moral and prosocial behavior patterns, developing interest in classic literature, and creative self-realization.